The Success of Ovulation Induction with Letrozole and Gonadotropins in Obese and Nonobese Women: A Study from a Tertiary Center - Vaidyanathan Gowri; Arwa Al-Amri; Thikra Mohammed Abdulrahman Almamari; Maha Al Khaduri; Sanjay Jaju (Hindawi Limited, 2022)
Background. Letrozole, an aromatase inhibitor, is suggested as a first-line drug for ovulation induction in women with polycystic ovary syndrome (PCOS) especially in obese women. Letrozole has also been used in women with unexplained infertility with similar rates of success to clomiphene. However, literature on letrozole and gonadotropins in obese and nonobese women is sparse. Hence, this study was done to assess the success of ovulation induction (OI) with letrozole plus follicle stimulating hormone (FSH) in obese (BMI≥30 kg/m2) and nonobese women (BMI<30 kg/m2). Methods. A retrospective descriptive cohort study was conducted involving 135 women who underwent OI with letrozole plus follicle stimulating hormone therapy and either timed intercourse or intrauterine insemination. The data was collected from the hospital information system, including the age, body mass index, the type of infertility, number of induction cycles with letrozole, number of gonadotropin injections, and the pregnancy occurrence following treatment. SPSS was used to analyze the data. Results. There were 135 women who used FSH injections along with letrozole. Of this, 28.5% obese women got pregnant compared to 29.2% nonobese women, but this did not attain statistical significance (P=0.75). About 70% of obese women and 57% on nonobese women had polycystic ovarian syndrome. The median number of FSH injections was six, and the interquartile range was 3 to 11. Conclusion. Of the 135 women undergoing letrozole and FSH, there was almost an equal probability of pregnancy in the obese group (BMI≥30 kg/m2) and nonobese women.